Selection of exopolysaccharide-producing lactic acid bacteria isolates from Inner Mongolian traditional yoghurt - Zhang Chun-lei; Li Jia-qi; Guo Hai-tao; Wang Jie; Xu Ri-hua (Mljekarstvo)
Lactic acid bacteria (LAB) isolated from Inner Mongolian traditional yoghurt were evaluated for the production of exopolysaccharides (EPS) by phenol-sulphuric acid method after ethanol precipitation and dialysis. Total polysaccharide was extracted from sucrose-containing MRS broth cultures of the selected LAB strains. Comparison of the EPS yields revealed that among tested LAB, strain 37 exhibited the highest production of 536.904 mg/L. The strain was identified as Leuconostoc citreum with carbohydrate assimilation profiling, 16S rRNA and pheS gene sequencing. The Ln. citreum 37 was found to be a novel EPS producing strain. It was found that there was no direct linear relation between the colony size and EPS yield, so the colony size could not to be used to screen EPS-producing strains.